13. OUTCOMES OF BREAST RECONSTRUCTION USING LATISSIMUS DORSI FLAP FOLLOWING MASTECTOMY FOR STAGE I-II BREAST CANCER AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of breast reconstruction using latissimus dorsi flap following mastectomy for stage I-II breast cancer at Military Hospital 175.Subjects and Methods: A descriptive study combined with a clinical interventional approach, without a control group, was conducted on 46 patients diagnosed with stage I-II breast cancer who underwent breast reconstruction using a latissimus dorsi flap following mastectomy at Military Hospital 175, from January 2022 to October 2024.Results: The study on 46 patients with stage I-II breast cancer revealed that the majority of cases occurred in the left breast (52.2%), with the most common tumor location being the outer upper quadrant (30.4%). Tumor sizes of 1-3 cm accounted for the highest proportion (69.6%). The survival rate of the flap was 95.7%, with complications including seroma formation (21.7%), surgical site infection (8.7%), and partial flap necrosis (4.3%), while no cases of total flap necrosis were recorded. Patient satisfaction with aesthetics was high, with 32.6% being very satisfied and 43.5% satisfied. Regarding functional recovery, 76.1% of patients achieved a DASH score of 0-25, indicating good shoulder mobility, and no severe limitations were observed.Conclusion: Breast reconstruction using latissimus dorsi flap demonstrated positive outcomes with low complication rates and good recovery, ensuring both aesthetic and functional results. This method is a suitable option for stage I-II breast cancer patients, contributing to improved quality of life.
Keywords: Mastectomy; breast reconstruction; latissimus dorsi flap.